Working Memory Function Enhancement Intervention Using Padjadjaran Memory Rehearsal Application in Children with Mild Intellectual Disability - Ita Novita Br. Purba; Langgersari Elsari Novianti; Lenny Kendhawati (PSIKODIMENSIA, 2020)
This research was aim to investigate the enhancing of working memory function of children with mild intellectual disability with 6-7 years old mental age after intervention with Padjadjaran Memory Rehearshal Application (PMRA) Padjadjaran Memory Rehearshal Application (PMRA), with assessed their performance in other task that did not give in intervention, digit span and Knox cube. This research used Quasi Experiment Within Subject Design, which involved 5 children with mild intellectual disability with 6-7 years old mental age. The data analysis used Wilcoxon Matched-Pairs Signed-Ranks, the Digit Span task and Knox Cube showed that PMRA could enhance the phonological loop (Tobs=Ttab) but did not enhance visuo-spatial component (Tobs>Ttab). PMRA can be used to enhance participant’s working memory function in holding and using information that processed verbally.